Profiling half-back play in rugby union and the impact of substitutions - Hughes, M.; Smyth, G. (Journal of Human Sport & Exercise, 2018)
An exploratory method of quantifying the impact of individual players in rugby union was developed and applied to both half-back positions in 2015 Rugby World Cup matches with a view to firstly test the validity of these systems by profiling players, and secondly, if successful, to assess the impact of substitutions. A match impact scoring system was devised using questionnaire responses of an expert group of professional rugby analysts and experienced international coaches. The scoring system weighted each game action in a positive or negative manner according to the impact on team performance. It was found that the proposed method produced valid and reliable data concerning player performance. It was applied to half-backs substituted with more than 20 mins playing time left, the two 20 min period, before and after substitution, were compared. A "non-substituted" control group were also analysed, in both the first and final 20 minutes of competition. It was found that for the scrum-half position, the starting players produced a higher median `efficacy` score than replacement players 27.46, (std. dev. +10.06) and 20.42, (+12.45). The best performing scrum-half group were the 60-80 minute non-replaced players 29 (+9.0). For the out-half position, it was found that the highest median `efficacy` was achieved by the replacement player group 18.80, (+ 11.00), with the non-replaced 60-80 minute group performing worst 14.40, (+ 7.09). Future research should develop the methods applied in this study to define player profiles for each position on the rugby field. It is suggested that these profiles should use score difference between the teams to take into account the strength of the teams involved. The concept of a weighted individual player efficacy system has been demonstrated in the sport of rugby union, but could be applied in any team sport where greater individual player performance data is required.